Exploring Current Challenges on Security and Privacy in an Operational EHealth Information System - Denkovski, Viktor; Stojmenovska, Irena; Gavrilov, Goce; Radevski, Vladimir; Trajkovik, Vladimir (My University, 2024)
Bearing in mind that patient data is extremely sensitive, it is crucial to establish strong protection when the security and privacy of healthcare data are concerned. Prioritizing data security and privacy is essential for the overall healthcare industry in order to maintain the reliability of electronic healthcare (eHealth) information systems. This study explores the gathered data and information from the surveys and interviews by looking at the security and privacy concerns in using eHealth information technologies. The surveys and interviews were performed on the medical practitioners in N. Macedonia. The main goal is to find out how well-informed are the medical practitioners on the already in-place privacy measures that have been implemented by the medical authorities and to assess their attitudes regarding the need for additional improvements of the system. From the executed interviews, eight healthcare professionals participated in a thorough email interview in order to discover security and privacy issues associated with eHealth systems usage. This information served as the groundwork for administrating an online survey, to which 370 medical practitioners responded from primary and secondary healthcare. The findings emphasize how essential it is to promptly address the system usability concerns on the security and privacy procedures that are implemented when using eHealth technologies.
Keywords: eHealth Information System Security and Privacy Issues Medical Providers eHealth Challenges